Plant Recovery after Metal Stress—A Review - Jagna Chmielowska-Bąk; Joanna Deckert (Plants, 2021)
Contamination of the environment with metals, their adverse impact on plant performance and transmission to the human food chain through crops and vegetables are important concerns worldwide. Although the literature on metal contamination, toxicity and plant response to this stress factor is quite abundant, there are very limited reports on the phenomenon of plant recovery after metal stress. The present article reviews available literature on the recovery process examined in various plant species, in response to several metals (Al, Cd, Cu, Ni, Pb, Zn), applied at different concentrations and treatment duration. The reviewed studies have been carried out in laboratory conditions. However, it should be highlighted that although metal stress is not as transient as most of other stress factors (e.g., drought, heat, chilling), metal concentration in the soil may still decrease due to, e.g., leaching to lower soil layers or uptake by organisms. Thus, in natural conditions, plants may be subjected to post-metal-stress conditions. The review also discusses the mechanism behind efficient recovery and the impact of post metal stress on future plant performance—possible acquisition of stress memory, adaptation to unfavorable conditions and cross-tolerance towards other stress factors.